Bullying among youth from eight African countries and associations with adverse health behaviors. Issue 3 (June 2008) - Brown, David W; Riley, Leanne; Butchart, Alexander; Kann, Laura
Bullying is a form of youth aggression associated with more serious violent behaviors and with an increased likelihood of physical and psychosomatic health problems. Studies describing the burden of bullying and relationships with adverse health behaviors among youth in Africa are lacking. Using data from the Global School-based Student Health Survey, we estimated the prevalence of exposure to bullying among youth from Kenya, Namibia, Morocco, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe and examined associations with measures of mental health, tobacco use, alcohol and drug use, and sexual behaviors. Exposure to bullying behavior was common among the boys and girls. We observed consistent, strong and graded relationships between exposure to bullying behavior and multiple adverse health-risk behaviors.